Crescent-Moon Beam-To-Column Connection for Precast Industrial Buildings - Bressanelli, Michele Egidio; Bosio, Marco; Belleri, Andrea; Riva, Paolo; Biagiotti, Piergiovanni (Frontiers in Built Environment, 2021)
The 2012 Emilia earthquakes caused significant damage to existing precast reinforced concrete (RC) industrial buildings not specifically designed to resist seismic actions. The main collapses were related to the loss of support of beams and roof elements caused by high relative displacement, failure of the mechanical connections and consequent fall of cladding panels, damage at the base of the columns and collapse of RC forks at the top of the columns. In all cases, the behaviour of the connections, and specifically of beam-to-column connections, demonstrated to be crucial, given that they may inhibit the exploitation of strength and ductility reserves in precast elements. This paper presents a dissipative beam-to-column connection restraint-device for precast industrial buildings. The device can be applied to existing structures to transfer horizontal seismic forces between beams and columns and to increase the energy dissipation of the system. Design criteria were defined with the aim to limit the relative maximum displacement at the beam-to-column interface and to mitigate the out-of-plane overturning of the beam which can lead to the frame collapse. Numerical analyses were carried out to define a suitable shape of the device and to investigate its effectiveness in terms of both local and global behaviour. To validate the computational results, experimental tests were also carried out. The tests allowed to classify the device as “dissipative” according to UNI EN 15129. Finally, the design procedure has been validated by reference to a case study consisting of a one-story industrial building designed in accordance with the Italian building code.